Formal requirements modeling with executable use cases and Coloured Petri Nets - Jorgensen, Jens B. (2009)
This paper presents executable use cases (EUCs), which constitute a model-based approach to requirements engineering. EUCs may be used as a supplement to model-driven development (MDD) and can describe and link user-level requirements and more technical software specifications. In MDD, user-level requirements are not always explicitly described, since usually it is sufficient that one provides a specification, or platform-independent model, of the software that is to be developed. Therefore, a combination of EUCs and MDD may have potential to cover the path from user-level requirements via specifications to implementations of computer-based systems.